2022
DOI: 10.1039/d1ma00809a
|View full text |Cite
|
Sign up to set email alerts
|

Atomically dispersed Co–N–C electrocatalysts synthesized by a low-speed ball milling method for proton exchange membrane fuel cells

Abstract: Atomically dispersed cobalt-nitrogen-carbon (Co-N-C) catalysts have appeared as the potential substitutes to the costly noble-metal catalysts for the oxygen reduction reaction (ORR) in proton exchange membrane fuel cells (PEMFCs). After...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…26,44 On this basis, our group found that the ordinary deionized water could play the same role as LAG, which was more convenient and less expensive than the above agents. 13,21 By comprehensive consideration, the hydrogen atom might be the key factor. 45,46 To further explore this phenomenon, we replaced deionized water with D 2 O during the synthesis of ZIF-180 and the consequent product was denoted as ZIF-D. As expected, ZIF-D took on the identical structure of ZIF-180 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26,44 On this basis, our group found that the ordinary deionized water could play the same role as LAG, which was more convenient and less expensive than the above agents. 13,21 By comprehensive consideration, the hydrogen atom might be the key factor. 45,46 To further explore this phenomenon, we replaced deionized water with D 2 O during the synthesis of ZIF-180 and the consequent product was denoted as ZIF-D. As expected, ZIF-D took on the identical structure of ZIF-180 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 In the eld of metal-nitrogen-carbon ORR electrocatalysts, the liquid-assisted mechanochemical grinding or milling has been proven feasible for preparing single atom metal-N-C catalysts. 21 However, when it comes to ZIF-8 based Fe-N-C electrocatalysts, it is of great challenge to disperse low-molecular-mass Fe sources, such as ferric nitrate, uniformly in the ZIF-8 precursor, while the agglomeration results in disappointing ORR performance. 22 Conversely, when using highmolecular-mass Fe sources, such as iron-based MOFs, it is extremely difficult to determine the optimized amount of Fe in the precursor, hindering the precise and ingenious design of Fe-N-C catalysts for high-class ORR properties.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting milled mixtures were calcined at 400 • C for 2 h. He and co-workers [169] have successfully produced Pd 1 /ZnO, Ru 1 /ZnO, Rh 1 /ZnO, and Pd 1 /CuO via the afore-proposed procedure. Interestingly, no significant scaling-up effect was observed as the kg-scale, Pd 1 /ZnO exhibits almost the same catalytic performance (about 92% styrene yield via hydrogenation of phenylacetylene) as compared to the small-scale fabrication (10 g-scale) under the same conditions (10 mg of catalyst and 0.5 mmol of phenylacetylene were used, the reaction was conducted for 20 min at a temperature of 50 • C) The ball-milling method has been successfully applied to the fabrication of SACs for oxidation of benzene [99], hydrogenation of acetylene [170], phenylacetylene [169], 2-methyl-3-butyn-2-ol [171], glycerol hydrogenolysis [172], organic pollutant degradation [173], Fenton-like reaction [174], HER [175], ORR [176,177], CO oxidation [169], and photoreaction [128]. Nevertheless, (a) restricted scalability especially for co-catalyst synthesis which inevitably involves liquid-phase processes [128]; and (b) the occurrence of metallic impurities from the machinery on the catalysts are the other common weaknesses of this approach [178].…”
Section: Deposition-precipitationmentioning
confidence: 99%
“…• Al 2 O 3 [321] • Carbon/Graphene [59,177,236,353,423] • Carbon nitride [424,425] • MnO 2 [424] • MoS 2 [426] • N 3 P 1 site [427] • SiO 2 [426,428] • TiO 2 [426] • ZnO [361] • ALD [423] • Ball milling [353] • Electrochemical method [425] • Freeze-drying method [59] • Mass-selected soft-landing [236] • Pyrolysis-assisted method [211,426,427,429,430] • Redox-driven hydrolysis [431] • Sol-gel method [361] • Thermal emitting strategy [214] • Thermal polymerization [424] • Wet impregnation [321,426,428] ,…”
Section: Comentioning
confidence: 99%
“…Wang et al [55] also reported a combined preparation method of ball-milling with an additional pyrolysis treatment, leading to Co nanoparticles on C-N nanosheets with good catalytic performance in a wide pH range. Other works have also focused on the preparation of Co-N-C catalysts by following similar strategies [56]. Interestingly, ball-milling has been reported to promote stronger intermolecular π-π interactions and good MPc distribution in metal phthalocyanines on carbon materials [52,54].…”
Section: Introductionmentioning
confidence: 99%